A review on the effect of amination pretreatment for the selective separation of CO2. (15th November 2015) - Adelodun, Adedeji Adebukola; Kim, Ki-Hyun; Ngila, Jane Catherine; Szulejko, Jan
Highlights: A review of surface chemical characteristics of activated carbon (AC) is provided. The significance of enhanced surface energy through amination of AC is described. Pretreatment prior to amination is assessed to improve selective adsorption of CO2 . The efficiency of different adsorbents is assessed for CO2 adsorption. KOH is found to be the most efficient pre-treatment for improving amination. Abstract: For the cost-effective control of unregulated CO2 emissions, its capture through modifications to adsorbents has recently gained much attention. In this respect, amination through basification of activated carbon (AC) surface is one of the practical approaches to separate CO2 . To learn more about such mechanism, a number of key variables (e.g., the nature of the AC surface groups, their CO2 absorption enthalpy, and the effect of amination on adsorption) are reviewed. The potent role of amination is hence described with respect to the significance of pretreatment prior to amination technique by comparing the performance of diverse media (e.g., advanced oxidation processes (AOP), Ca(NO3 )2, and KOH) for such application. The analysis of collected adsorption data suggests that the efficiency of amination and eventual selective adsorption of CO2 can be improved by such pretreatment as KOH sintering in terms of inducing stronger surface CO2 binding energy.